Impacto das mudanças climáticas na estrutura de custos das firmas de abastecimento de água da região Norte do Brasil - Rezende, Lucas André Matos Sarraff de (Brasil, 2023)
Basic sanitation is a basic right of every Brazilian citizen and has a direct impact on the health, well-being, and social balance of people. On the other hand, living in an environmentally healthy environment is also a right guaranteed by the Federal Constitution. Climate changes, such as variations in temperature and precipitation, affect water treatment, impacting the costs of water supply companies. According to 2020 data from the National System of Information on Sanitation (SNIS), 84.1% of the Brazilian population is supplied with treated water, while in the North region of the country this percentage is only 58.9%. The overall objective of this study is to analyze the impact of climate change on the cost structure of water supply companies in the North region of Brazil, in the period from 2008 to 2020. Data collection was done through the SNIS, the database of the University of Delaware, and MapBiomas. A Cobb Douglas cost function was estimated using log-log and log-lin regression techniques to analyze the impact of climate variables (temperature and precipitation) and vegetation coverage. The results showed that the climate variables and vegetation coverage impact the variable cost of production of water supply companies in the North region of Brazil. Additionally, it was found that higher precipitation levels reduce costs, and expenses for chemicals have a significant impact on the cost structure, indicating that the high amount of organic matter in the waters, due to the region's specificities, requires more expenses.